The Inner Leader in Transformative Leadership: Personal Transformation through Trauma Integration and Spiritual Development - Briciu, Bianca (GILE Journal of Skills Development, 2024)
This article analyzes the role of personal transformation in the context of transformative leadership, focusing on the processes of trauma integration and spiritual development. Trauma integration facilitates access to the inner leader through a gradual process of increasing awareness of unconscious patterns. Spiritual development expands consciousness developing the capacity to hold in awareness both the inner and the outer world, contributing to the self-transforming mind, an open and adaptive engagement with the world. These two aspects of personal development support leaders to de-construct oppressive structures in their own consciousness and engage in awareness-based social transformation. Trauma integration and spiritual development contribute to the Being dimension of the Inner Development Goals framework, creating access to the inner compass and increasing self-awareness, authenticity, openness and presence.